(untitled) (Medical Forum Monthly, 2022)
Objective: To develop a data collection instrument that can measure the observance of Islamic Work Ethics in health professional academicians, because lack of such a questionnaire was observed in the academic literature. Study Design: A mixed-methods exploratory study Place and Duration of Study: This study was conducted at the Riphah International University and HITEC-IMS, Taxila during a period of 6 months from April to September 2021. Materials and Methods: A tentative questionnaire was designed by combining the qualitative data from focus group discussions with literature. The tentative questionnaire was then refined during the subsequent stages of a modified Delphi study, conducting cognitive pre-testing interviews and pilot testing of the novel instrument. Results: The tentative questionnaire developed via Delphi study was then refined by conducting cognitive pre-testing interviews to ensure the prospective respondents easily and clearly understood the questionnaire items in the same manner as the primary researcher designed them. Pilot testing of the novel instrument was then performed to establish its reliability. Conclusion: A data collection instrument was developed following the guidelines as put forth in the academic literature. The instrument developed is reliable and fit for purpose. The instrument can be utilised to measure the observance of Islamic work ethics in health professional academics, and necessary actions can be taken to reinforce ethical behaviours and remedy unethical behaviours.